Space-time variability factors from air pollution inside Paris by CO measurement - Quénol, Hervé; Bridier, Sébastien; Frangi, Jean Pierre; Beltrando, Gérad; De Rosny, Giles (ERDKUNDE, 2006)
Airparif (air quality network) informs the Parisian population about air quality through the ATMO index, which provides information on the agglomeration scale. The aim of this study is to develop the possibilities of observation, at individual scale 1), in order to upgrade the data collected on a regional scale through information of proximity 2). We observed the air pollution caused by automobile traffic, which is a main contributor to bad air quality in Paris and its suburbs, through CO measurements. The installation of mobile and fixed measurements, adapted on fine space scales, made it possible to observe the spatio-temporal CO variability. Fixed measures carried out at six stations between October 2001 and February 2002 highlight that daily CO distribution presents a similar profile at all stations, having a first peak in the morning (between 8 and 9 a.m.) and then a second peak at the beginning of the evening (between 7 and 8 p.m.). But the CO concentration varies strongly between the stations. The itinerant measurements carried out at a small spatial and temporal scale (a few meters and a few seconds) highlight a strong variability of the CO concentration. Near a traffic light the CO concentration increases up to 25 times more between the phases where light is green and red. The CO level between a pedestrian street and a nearby street with important traffic can be multiplied by 10. Variability of this marker is conditioned by the characteristics of traffic, the proximity of traffic, urban morphology and weather conditions. This information contributes to the definition of a proximity index, taking into consideration the whole number of data (Airparif network, traffic level and weather data) and an analysis on fine-scale districts.